Pengaruh Good Corporate Governance dan Karakteristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Aurellia Adi Leksono; Sansaloni Butar Butar (Universitas Katolik Soegijapranata Semarang, 2018)
This study examine the role of good corporate governance (GCG) and firm characteristics to expand corporate social responsibility (CSR) disclosure. CSR disclosure is measured by fraction of total items reported in Sustainability Report to 58 items index released by Global Reporting Initiative. Samples are collected from listed companies in BEI (Bursa Efek Indonesia) and have been participated in Indonesian Sustainability Report Award (ISRA during 2014-2016. As much as 22 companies have complete data for further analysis. Using multiple regression analysis, results showed that profitability have a positive effect on CSR disclosure and become the only accepted hypothesis in this research; size of board of commissioner, company size, and leverage have no effect on CSR disclosure; while audit committee meeting frequency have negative effect on CSR disclosure.